Pengaruh Kompleksitas Pelaporan Akuntansi terhadap Kualitas Audit : Peran Rotasi Mitra dan Jasa Non-Audit - Muhammad Rizal; Farah Qalbia; Eri Kusnanto (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2024)
This study aims to examine the impact of accounting reporting complexity on audit quality, considering the moderating role of audit partner rotation and the use of non-audit services. Through a qualitative literature review approach, this research analyzes various previous studies to explore the relationship between these factors in the context of auditing. The findings indicate that accounting reporting complexity can increase challenges for auditors in maintaining audit quality. Meanwhile, audit partner rotation can improve auditor independence but may reduce audit quality if done too frequently. The use of non-audit services, while providing additional insights, may lower audit quality if not strictly regulated. This study provides valuable insights for practitioners and policymakers in managing these factors to enhance audit quality.